A imigração, a etnografia e a ética - Radhay, Rachel Anneliese (Cadernos de Linguagem e Sociedade, 2010)
The relation between discourse and power in Brazilian immigration is complex. There is the public sphere with the State’s immigration officials. There are also migrants in the intricacies of their worlds. Discourse and power refer to hierarchies of contexts and relations in which multiple truths are constructed vis Ã  vis immigration. There is marked discrimination in the representation and evaluation of immigrants. Those with high investments or specialist knowledge are welcome whilst those who are socially underprivileged are valueless. All these issues can be considered through ethnography. However, delving ethnographically into the complexities of immigration stirs up ethical issues.